The Effect of Nurses' Perception of Disaster Preparedness on Individual Disaster Resilience - Katrancı, Nilgün; Kuşcu Karatepe, Hilal (Sağlık ve hemşirelik yönetimi dergisi (online), 2024)
Introduction: It is important for nurses to be prepared for disasters in order to develop resilience in reducing the possible risks of disasters and coping with their effects. Aim: The aim of this study was to determine the effect of nurses' disaster preparedness on individual disaster resilience. Method: The descriptive and cross-sectional study was conducted in a sample of 174 nurses working in public and private hospitals in the provinces that experienced the February 6, 2023 Kahramanmaraş-centered earthquake. "Personal Information Form", "Perception of Disaster Preparedness Scale of Personnel Working in Prehospital Emergency Health Services" and Individual Disaster Resilience" scales were used as data collection tools. Data were obtained by snowball sampling method through online applications such as WhatsApp, Instagram and e-mail. Descriptive statistics, Cronbach Alpha coefficient, Pearson correlation, simple and multiple regression analysis were preferred in the evaluation of the data. Results: The mean score of the nurses' disaster preparedness scale overall was 3.87 (SD=0.44) and the mean score of the individual disaster resistance scale overall was 3.59 (SD=0.40). The model created to determine the effect of nurses' disaster preparedness on individual disaster resilience has a statistically significant and positive effect (β: ,478) and the variance explained is 22.8% (R2 =0.228; F=50.880; p<0.01). Conclusion: It was found that the disaster preparedness and individual disaster resilience of the nurses were above average and disaster preparedness affected their disaster resilience. As the disaster preparedness of the nurses increased, also their resilience increases.